Optimalisasi Sistem Sertifikasi Halal Indonesia Untuk Mendukung Standar Internasional dan Kepuasan Konsumen Global - Alfiana Yustia; Ahmad Sidiq; Dicko Syah Purnama Putra; Muhammad Ersya Faraby; Hawa Gazani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study discusses the effectiveness of Indonesia's halal certification system in supporting international standards and increasing global consumer satisfaction. The study uses a descriptive qualitative method with a case study approach to analyze the implementation of the national halal certification system. The results show that the halal certification system has strengthened legal protection and consumer confidence in halal products through synergy between BPJPH, MUI, and LPH. However, there are still challenges in harmonizing halal standards between countries and increasing the recognition of Indonesian certification at the global level. The digitization of the certification process and integration with international standards are considered important to accelerate services and enhance the credibility of the national system. This study recommends strengthening collaboration among stakeholders, international halal diplomacy, and technology-based system innovation so that Indonesia can compete globally and play a role as a world halal certification center